Antibacterial activity and mechanism of action of 3'-azido-3'-deoxythymidine (BW A509U). - Elwell, L P (1987)
The thymidine analog 3'-azido-3'-deoxythymidine (BW A509U; azidothymidine [AZT]) had potent bactericidal activity against many members of the family Enterobacteriaceae, including strains of Escherichia coli, Salmonella typhimurium, Klebsiella pneumoniae, Shigella flexneri, and Enterobacter aerogenes. AZT also had bactericidal activity against Vibrio cholerae and the fish pathogen Vibrio anguillarum. AZT had no activity against Pseudomonas aeruginosa, gram-positive bacteria, anaerobic bacteria, Mycobacterium tuberculosis, nontuberculosis mycobacteria, or most fungal pathogens. Several lines of evidence indicated that AZT must be activated to the nucleotide level to inhibit cellular metabolism: AZT was a substrate for E. coli thymidine kinase; spontaneously arising AZT-resistant mutants of E. coli ML-30 and S. typhimurium were deficient in thymidine kinase; and intact E. coli ML-30 cells converted [3H]AZT to its mono-, di-, and triphosphate metabolites. Of the phosphorylated metabolites, AZT-5'-triphosphate was the most potent inhibitor of replicative DNA synthesis in toluene-permeabilized E. coli pol A mutant cells. AZT-treated E. coli cultures grown in minimal medium contained highly elongated cells consistent with the inhibition of DNA synthesis. AZT-triphosphate was a specific DNA chain terminator in the in vitro DNA polymerization reaction catalyzed by the Klenow fragment of E. coli DNA polymerase I. Thus, DNA chain termination may explain the lethal properties of this compound against susceptible microorganisms.